Progressivism Philosophy in Education: A Conceptual Analysis and Its Implications for 21st-Century Learning Practices: (Filsafat Progresivisme dalam Pendidikan: Analisis Konseptual dan Implikasinya terhadap Praktik Pembelajaran Abad ke-21) - Naufal Akmal Syammary; Amri Yahya; Hanik Mahliatussikah (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2025)
Progressivism is a school of modern philosophy of education that wants a progressive, innovative, flexible, open, rational, and scientific nature that always adapts to the times. This study aims to analyze in depth the philosophy of progressivism and how this approach has implications for educational practice in the 21st century. This research uses a descriptive qualitative approach through the Systematic Literature Review (SLR) approach. The results of this study show that the philosophy of progressivism has exerted a significant influence on educational practice. This can be seen from the implications: 1) for the curriculum, has desired the flexibility of educational institutions in exploring the intelligence and abilities of students democratically, flexibly and pleasantly so as to create a flexible, free and open curriculum concept, 2) to educators, providing openness in designing models, strategies, approaches, methods, and fun learning media, so that educators are able to present learning concepts Effective and efficient, 3) to students, providing opportunities for them to develop progressively in developing their talents and potential in improving their skills and competencies.